2017
DOI: 10.1111/mpp.12564
|View full text |Cite
|
Sign up to set email alerts
|

A spatial temporal analysis of the Fusarium graminearum transcriptome during symptomless and symptomatic wheat infection

Abstract: SummaryFusarium head blight of wheat is one of the most serious and hazardous crop diseases worldwide. Here, a transcriptomic investigation of Fusarium graminearum reveals a new model for symptomless and symptomatic wheat infection. The predicted metabolic state and secretome of F. graminearum were distinct within symptomless and symptomatic wheat tissues. Transcripts for genes involved in the biosynthesis of the mycotoxin, deoxynivalenol, plus other characterized and putative secondary metabolite clusters inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 51 publications
8
79
0
Order By: Relevance
“…During the symptomless phase, extensive Fg transcriptional changes occur, which are distinct from those observed during the symptomatic phase (Brown et al ., ; Lysøe et al ., ). These include the rapid activation of various Tri genes, responsible for trichothecene and DON production, other co‐regulated gene clusters and non‐clustered genes of known and unknown functions.…”
Section: Fusarium Head Blight/scab Diseasementioning
confidence: 99%
“…During the symptomless phase, extensive Fg transcriptional changes occur, which are distinct from those observed during the symptomatic phase (Brown et al ., ; Lysøe et al ., ). These include the rapid activation of various Tri genes, responsible for trichothecene and DON production, other co‐regulated gene clusters and non‐clustered genes of known and unknown functions.…”
Section: Fusarium Head Blight/scab Diseasementioning
confidence: 99%
“…Mycotoxin contamination of foods and feedstuffs caused by phytopathogenic fungi, such as Fusarium spp., poses an almost intractable problem in agricultural production (Doll and Danicke, ). Fusarium species can infect the majority of crop plants, and virtually all cereals such as wheat, barley and maize (Brown et al , ; Osborne and Stein, ). Current strategies to protect crops from Fusarium infections include fungicide application for both disease control and limitation of mycotoxin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…This implied that FgTmfI may also regulate the expression of a number of transporter genes, in addition to its direct regulation on the expression of FgMYO1 for tolerance to phenamacril. Given that the ΔFgTfmI mutant showed a significant defect of virulence, we analyzed potential virulence‐related genes regulated by FgTfmI using previous F. graminearum transcriptomes measured in planta . Results demonstrated that a total of 20 genes with increased transcript abundance during wheat infection were found to be downregulated in the ΔFgTfmI mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the ΔFgTfmI mutant showed a significant defect of virulence, we analyzed potential virulence-related genes regulated by FgTfmI using previous F. graminearum transcriptomes measured in planta. 41,42 Results demonstrated that a total of 20 genes with increased transcript abundance during wheat infection were found to be downregulated in the ΔFgTfmI mutant ( Fig. S3, Table S2).…”
Section: Rna-seq Analysis With the Fgtfmi Mutantmentioning
confidence: 99%